Pelatihan perawatan/service AC untuk masyarakat sekitar Politeknik Penerbangan Indonesia Curug - Arnas, Yenni; M. Ismail, KGS.; Kurniawati, Zulina; Kurnianto, Benny; Haryadi Wibowo, Imam; Kalbuana, Nawang (Penamas: Journal of Community Service, 2021)
The trend of using air conditioners, air conditioners or called AC (Air Conditioner) is increasing in the community both in offices and in housing. To keep its performance, air conditioning should be maintained regularly according to the intensity procedure. Hence, the air conditioner can stabilize the air temperature and humidity of the area in accordance with its specification. As the demand for maintenance is growing, the opportunity to become an AC technician is also increasing. Carrying out basic training in AC maintenance can assist people who are interested to become AC technicians. Training participants are expected to gain knowledge of AC installation, AC components and working principles, AC maintenance, and safety standard.